1989
DOI: 10.1152/ajprenal.1989.257.6.f994
|View full text |Cite
|
Sign up to set email alerts
|

Sodium chloride and water transport in the thin descending limb of Henle of the quail

Abstract: Birds and mammals can produce hyperosmotic urine, but their renal morphology and urine-concentrating mechanisms differ. To elucidate the countercurrent urine concentration mechanism in birds, we examined the structure and transport properties of the descending limb (DL) of Henle of mammalian-type nephrons in Japanese quail, Coturnix coturnix. In the avian renal medulla, a prominent ring of collecting ducts and scattered thick limbs surrounds a core of capillaries and DLs. Epithelial cells in the upper DL (DLu)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 0 publications
6
40
0
Order By: Relevance
“…If urea is added to the medullary interstitium, the osmolality can be further increased without increasing tonicity because urea evenly distributes to both extracellular and intracellular fluid. In fact, mammals can concentrate urine more effectively than lower class vertebrates such as reptiles or birds, which do not accumulate urea in the renal medulla (4,19).…”
Section: Discussionmentioning
confidence: 99%
“…If urea is added to the medullary interstitium, the osmolality can be further increased without increasing tonicity because urea evenly distributes to both extracellular and intracellular fluid. In fact, mammals can concentrate urine more effectively than lower class vertebrates such as reptiles or birds, which do not accumulate urea in the renal medulla (4,19).…”
Section: Discussionmentioning
confidence: 99%
“…PT proximal tubule AVT arginine vasotocin. Reproduced with modification from Nishimura et al [58] and Osono and Nishimura [62] ( Fig. 1).…”
Section: Functional Morphology Of Avian Kidney and Urine Concentrationmentioning
confidence: 99%
“…They suggested a specific hypothesis for the operation of the avian concentrating mechanism, as a countercurrent multiplier system. They proposed that active transepithelial transport of sodium chloride from the thick epithelium of the ascending limb is the source of the single effect of the avian countercurrent mechanism (Nishimura et al 1989). The current study presents further information regarding the role of secretory units in urine production in some bird species.…”
Section: Discussionmentioning
confidence: 53%
“…Collecting ducts were separated by thick and thin loops of Henle throughout the medullary cones. Nishimura et al (1989) showed that the thin limb of the loop of Henle is operative in the countercurrent multiplication system. They suggested a specific hypothesis for the operation of the avian concentrating mechanism, as a countercurrent multiplier system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation